Fontes iuris gentium : digest of the decisions of the international court of justice 1976-1985 - Rudolf Bernhardt (Springer Verlag, 1990)
The series Fontes Iures Gentium has presented the decisions of the Permanent Court of International Justice, founded after World War I, and its successor, the International Court of Justice, a principal organ of the United Nations, up to 1975. This new volume represents the link to the present. The pronouncements which are of importance for international law from all of the judgements and advisory opinions of the Court, and from all separate and dissenting opinions of individual judges, have once again been systematically arranged and reproduced in the original language, English or French. Fontes Iures Gentium provides the reader with a reliable means of access to the decisions of the most important international judicial organ. Like its forerunners, the new volume includes subject indexes in three languages as well as lists of the decisions and judges.